Studi Fenomena Pendidikan Keagamaan Islam Multikultural di Pondok Pesantren Bustanul Mutaallimin Blitar - Shofwan, Arif Muzayin (STAI Asy-Syukriyyah, 2023)
Multicultural Islamic religious education is still echoed in several Islamic boarding schools, one of which is the Bustanul Mutaallimin Blitar Islamic Boarding School. This qualitative research with a phenomenological study will discuss the phenomenon of multicultural Islamic religious education at the Bustanul Mutaallimin Islamic Boarding School, Blitar. The data analysis technique used is descriptive-explorative involving four components, namely domain analysis, taxonomy, componential, and cultural themes. This study found the following two things. First, multicultural Islamic religious education is an educational strategy based on Islamic teachings that develop the ability to know each other, be tolerant, democratic, equal, and fair, help each other, respect each other, love each other, and be full of peace. Second, the content of multicultural Islamic religious education at the Bustanul Mutaallimin Blitar Islamic Boarding School is contained in the thoughts of the kiai, within the curriculum frame, both the traditional Islamic boarding school curriculum and the modern Islamic boarding school curriculum are based on the government curriculum (Ministry of Religion and Ministry of National Education), and are contained in seventeen Islamic boarding schools and eight twelve cultural cultures without national character that must be applied by every citizen in the pesantren environment.